2001
DOI: 10.1021/jp002511d
|View full text |Cite
|
Sign up to set email alerts
|

Unimolecular Reaction Kinetics of CF2ClCF2CH3 and CF2ClCF2CD3:  Experimental Evidence for a Novel 1,2-FCl Rearrangement Pathway

Abstract: Chemically activated CF 2 ClCF 2 CH 3 and CF 2 ClCF 2 CD 3 , containing 98.5 and 100 kcal/mol of internal energy, respectively, were formed in the gas phase from the combination of CF 2 ClCF 2 and CH 3 or CD 3 radicals, respectively. These radicals were generated from the UV photolysis of CF 2 ClCF 2 I and CH 3 I or CD 3 I. The decomposition products were CF 2 ClCFdCH 2 (CF 2 ClCFdCD 2 ) from a 2,3-HF (DF) elimination and CF 3 -CFdCH 2 (CF 3 CFdCD 2 ) suggesting a 1,3-HCl (DCl) elimination reaction. The 1,3-HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 31 publications
2
38
0
Order By: Relevance
“…It is interesting to compare our data with published pyrolysis studies of unimolecular elimination experiments on chemically activated mixed halogenated species [37][38][39][40][41][42][43][44][45][46][47][48]. In all these experiments HCl loss was dominant.…”
Section: Hx Elimination From Partially Fluorinated Polymersmentioning
confidence: 65%
See 2 more Smart Citations
“…It is interesting to compare our data with published pyrolysis studies of unimolecular elimination experiments on chemically activated mixed halogenated species [37][38][39][40][41][42][43][44][45][46][47][48]. In all these experiments HCl loss was dominant.…”
Section: Hx Elimination From Partially Fluorinated Polymersmentioning
confidence: 65%
“…In all these experiments HCl loss was dominant. For CClF 2 -CH 3 Jones et al [39] reported a branching ratio of 25:1 whereas, in the low-pressure limit, for CF 3 -CFCl-CH 3 the reported value was 13.5:1 in favour of HCl [43]. Pyrolysis studies reported branching ratios near 10:1 for CClF 2 -CH 3 .…”
Section: Hx Elimination From Partially Fluorinated Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…3,6 In previous work, the observation of CF 3 CFdCH 2 following excitation of CF 2 ClCF 2 CH 3 6 was claimed as identification of formation of CF 3 CFClCH 3 by the Cl-F interchange reaction. In the current work, the branching between the HF and HCl elimination channels of CF 3 CFClCH 3 was measured, and the preference of HCl elimination was verified.…”
Section: Introductionmentioning
confidence: 99%
“…8 We now wish to report a comprehensive study of the HCl and HF elimination reactions from the CF 3 CFClCH 3 molecule. This work is part of a systematic study of various fluorochloropropanes, [6][7][8] and the assigned threshold energies for CF 3 CFClCH 3 will be compared to that for HF elimination from CF 3 CF 2 CH 3 .…”
Section: Introductionmentioning
confidence: 99%